GERAKAN POLITIK PEREMPUAN PARTAI GOLKAR KOTA PEKANBARU PERIODE 2004 – 2009 DALAM MEMPERJUANGKAN KEPENTINGAN PEREMPUAN - Asrida, Wan; ', Wazni; Dewi, Chitra Puspita (Nakhoda: Jurnal Ilmu Pemerintahan, 2012)
Woman political participation on reform era is normal activity. Reform producted rules (Act aboutGeneral Election and Act about Political Party) which give space for woman political participation.Golongan Karya Party is one of strong political party in Indonesia that have commitment forwoman empowerment in politic which women cadrees have position as management of party andlegislative in Pekanbaru. There are problem that how woman can use opportunity as managementparty and legislative to fighting for woman interests by political movements. These politicalmovements have well-constructed activities (appropriate for woman interest), with woman?scollective as an institution, sense of solidarity, woman collective identity and continuity activities bysystematic in Golongan Karya Party.Keywords: Woman and Politic, Women Movement, Golongan Karya Party